Does intergroup contact affect personality? A longitudinal study on the bidirectional relationship between intergroup contact and personality traits. (18th October 2017) - Vezzali, Loris; Turner, Rhiannon; Capozza, Dora; Trifiletti, Elena
Abstract: We conducted a longitudinal study to test whether, in addition to being predicted by personality, intergroup contact is longitudinally associated with personality traits. Participants were 388 majority (Italian) and 109 minority (immigrant) first‐year high school students. Results revealed a bidirectional relationship between contact and personality: Quality of contact was longitudinally associated with greater agreeableness and openness to experience, whereas agreeableness and openness to experience were longitudinal predictors of contact quality. An unexpected negative longitudinal association also emerged between quantity of contact and agreeableness. These effects were not moderated by group of belonging (majority vs. minority). Our findings highlight the importance of integrating research on intergroup contact with research on personality.